2020
DOI: 10.1007/s11356-020-10402-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between extreme heat and hospital admissions for cataract patients in Hefei, China

Abstract: Cataract is the first cause of blindness and the major cause of visual impairment worldwide. Under conditions of global warming, researchers have begun to give attention to the influence of increasing temperature on cataract patients. Our paper aimed to investigate the association between extreme heat and hospital admissions for cataract in Hefei, China. Based on data from the New Rural Cooperative Medical System and National Meteorological Information Center, we used a generalized additive model and a distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Identification of pollution sources is a crucial stage in air quality management since it allows for better understanding of pollution control techniques and estimation of their respective contributions. [ 21–27 ] Modeling strategies involving source‐oriented or receptor models to associate emissions from pollution sources are referred to as source apportionment of particles. [ 28–34 ] Using robust mathematical tools, such data give essential knowledge for identifying and quantifying PM sources.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of pollution sources is a crucial stage in air quality management since it allows for better understanding of pollution control techniques and estimation of their respective contributions. [ 21–27 ] Modeling strategies involving source‐oriented or receptor models to associate emissions from pollution sources are referred to as source apportionment of particles. [ 28–34 ] Using robust mathematical tools, such data give essential knowledge for identifying and quantifying PM sources.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1906, the average global temperature has risen by 0.74 °C, and this trend is expected to accelerate over the next century. As global warming continues, worldwide extreme heat occurrences are growing, which is intimately related to the health and activities of humans (Xie et al, 2020). Exposure to heat, which will rise as a result of global warming, has been associated with an increased risk of a variety of cause-specific hospitalizations (Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Organizational commitment as an effective factor of emotional attachment or loyalty to the organization is a professional ability (Karami et al , 2017). Xie et al (2020) found that in case of shortage of HWs for epidemic treatment, HWs from other departments will come to support. However, even with this emergency back-up, some hospitals face other challenges in early identification and management crises such as lack of intensive care resources.…”
Section: Introductionmentioning
confidence: 99%